Pertentangan Antara Diskresi Kebijakan Dengan Penyalahgunaan Wewenang Dalam Tindak Pidana Korupsi - Nur Kumalaningdyah (Fakultas Hukum Universitas Islam Indonesia, 2019)
This study aims to determine the relationship between policy discretion and abuse of authority by public officials that lead to corruption. This is a normative legal research that was conducted through literature study that is relevant to the problem at hand. The results of the study concluded that in accordance with the unlawful nature (wederrechtelijkheid) as a limitation of the authority of public officials in carrying out policies (discretion) without relying on the legislation; discretion may be considered an abuse of authority if it defies Law Number 30 of 2014 on Government Administration.